The history of the management of sternal osteomyelitis and mediastinitis – from Hippocrates until today - Ennker, Ina Carolin (GMS Interdiscip Plast Reconstr Surg DGPW, 2014)
Even during the time of Hippocrates, Galen and their colleagues recognized mediastinal affections. However, they were not considered with the surgical treatment. First progress in the treatment options of this severe disease, still denoted as ‘terra incognita’, over to today’s gold standard are pictured. The mediastinitis-registry which was founded by the German Society for Thoracic and Cardiovascular Surgery (DGTHG) in 2011 and the recent establishment of the study group to adopt a guideline ‘diagnosis and therapy of postoperative mediastinitis/sternal osteomyelitis following cardiac surgery’ are attempts to a standardization of the treatment. Substantial advancement in the treatment of postoperative mediastinitis could be achieved in the past. The mortality dropped as low as less than 10%. With these implementations more benefit for the patients’ outcome can be expected.